Mitochondrial dysfunction and autophagy activation underlie NK cell impairment induced by Cannabis - Andrée-Ann Bolduc; Tony Tremblay; Mikhlid H. Almutairi; Abdelhabib Semlali; Lionel Loubaki (PLoS ONE, 2026)
Cannabis use continues to rise in Canada, prompting concerns due to its potential impact on immune function. This study investigated the effect of a cannabis joint extract (CJE) on natural killer (NK) cells and explored the mechanisms underlying its potential anti-inflammatory properties. Peripheral blood mononuclear cells (PBMCs) were exposed to varying concentrations of CJE to assess cytotoxicity. Flow cytometry was employed to evaluate oxidative stress, autophagy, mitochondrial membrane potential, caspase-3 activation, and DNA damage. Additionally, NK cell cytotoxicity, migration, and adhesion were analyzed. Data indicated that CJE exposure led to dose-dependent cytotoxicity in NK cells, primarily through apoptosis. Specifically, at a concentration of 3 μg/mL, CJE significantly increased reactive oxygen species (ROS), autophagy markers, caspase activation, and DNA damage, while reducing mitochondrial membrane potential. Moreover, CJE impaired NK cell-mediated killing of HeLa cells, though their migratory and adhesive abilities were unaffected. These findings evidence that cannabis can detrimentally affect NK cell viability and function via mechanisms involving autophagy and caspase-dependent apoptosis.